Exploring woodcarving markets to determine the potential of fiscal instruments for improving woodland management: the case of woodcarving in Southern Zimbabwe - Standa-Gunda, W.; Bond, I.; Campbell, Bruce M.; Petheram, L. (2007)
In many situations commercialization of forest products is based on common pool resources; often this leads to resource depletion. This paper investigates the potential of using fiscal instruments for institutional change to improve resource management where natural products are being marketed from common pool resources. Three markets along the Masvingo-Beitbridge Road in Southern Zimbabwe were studied. A simple model was produced to test the impact of fiscal instruments on the net revenue to carvers and the consequences for woodland management. The results suggest that there are few, if any options for the introduction of fiscal mechanisms to improve the management of the indigenous woodlands, and the creation of common-property institutions for the management of woodlands solely on the basis of financial incentives generated from woodcarving is highly unlikely.